The Sompoton mouthorgan of Sabah: embodying traditional knowledge, reflecting indigenous soundscapes - Jacqueline Pugh-Kitingan (Jabatan Warisan Negara, 2020)
Originating from Kampung Tikolod in the inland upland Tambunan District of Sabah, the Kadazan Dusun sompoton mouthorgan is traditionally played solo in non-ritual contexts for personal expression and entertainment. Over generations, it has been traded throughout Kadazan Dusun areas into other Dusunic cultures, as well as among Murutic and Paitanic peoples. Taking an ecomusicological approach and using photographic illustrations, this paper examines the construction and performance technique of the sompoton in terms of the traditional ecological and acoustic knowledge of the village performers who make the instrument. It then discusses sompoton music as a reflection of soundscapes from the surrounding environment. The paper concludes by showing how the partial destruction of the local environment and changes in local soundscapes with the introduction of new digital gaming media are affecting the enculturation of traditional knowledge andsompoton performance among younger generations.